PSYCHOPHYSIOLOGICAL CORRELATES OF SYSTEM–QUANTA OF COPING WITH A TEST BY STUDENTS - V. V. Andrianov (Сеченовский вестник)
The studies of the psychological and physiological ensuring of solving the multiple choice questions with different complication of the student were explored. Research of the psychological and physiological status of the medical students before and after solving the multiple choice questions with different complication were explored. Individual psychological and physiological parameters were studied in students. It was shown that there were mainly women and persons with right dominant hemisphere in the upper half of effective reiting. On the other hand, there were mainly man and persons with left dominant hemisphere among of lower half of effective reiting. This work has showed that effective result of solving training tasks depends on not only knowledge of theme, but of several psychophysiological parameters of students. There a not the connection between effective to perform systemoquants of multiple choice questions with different complication.